Properties of Characteristic Function of Commutative System of Unbounded Nonselfadjoint Operators - Zolotarev, V.A. (Журнал математической физики, анализа, геометрии, 2010)
A class of characteristic functions corresponding to commutative systems of unbounded nonselfadjoint operators is studied. The theorem on unitary equivalence is proved. The class of functions corresponding to these commutative systems of unbounded nonselfadjoint operators is described. There is obtained an analogue of the Hamilton{Caley theorem demonstrating that in the case of finite dimensionality of deficient subspaces there exists such a polynomial P (λ₁, λ₂) that annihilates the resolvents Rk = (Ak - αI)⁻¹; P (R₁, R₂) = 0.